The Risks Associated with Inhalation Exposure to Cosmetics and Potential for Assessment Using Lung Organoids - Yiguang Li; Xin Luo; Rong Hu; Lifeng Tang; Qi Xiang (Bioengineering)
This review addresses the exposure risks associated with the inhalation of aerosolized cosmetic products and explores the utility of lung organoids in assessing these risks. Aerosolized cosmetics such as sprays pose potential health hazards through inhalation, necessitating a thorough evaluation of exposure levels. Traditional methods for assessing inhalation risks have limitations, prompting the exploration of more sophisticated models. Lung organoids, three-dimensional structures derived from stem cells, offer a biologically relevant model for studying lung responses to inhaled substances. This review discusses the construction of lung organoids, their characteristics, and the advantages that they provide over conventional models. Furthermore, it examines existing studies that have employed lung organoids to evaluate the effects of cosmetic inhalation exposure, highlighting the potential of this approach to enhance the safety assessments of cosmetic products. We aim to establish lung organoids as a reliable tool for future research, ensuring the safety and regulatory compliance of cosmetics.